KAJIAN TIPE DAN BENTUK HUTAN KOTA KAWASAN DANAU RAJA KOTA RENGAT, KABUPATEN INDRAGIRI HULU, PROPINSI RIAU (Study on Type and Shape of Urban Forest in Danau Raja Area, Rengat City, Indragiri Hulu Regency, Riau Province) - Rachmad Hermawan; Nandi Kosmaryandi; Jojo Ontarjo (Media Konservasi, 2008)
Based on on the space use general plan of Rengat City year of 2003-2012, one of areas allocated for an urban green space is Danau Raja area. The area can be developed as an urban forest. The urban forest can increase aesthetical value, quality of urban environment and lead to a good image in sustainable development. Urban forest developed in the area is recreation type with the shape of a dispersed thing.Keywords: urban forest, type, shape